The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/ppul.26636
|View full text |Cite
|
Sign up to set email alerts
|

Lung function deficits and bronchodilator responsiveness at 12 years of age in children born very preterm compared with controls born at term

Cecilia Hagman,
Lars J. Björklund,
Leif Bjermer
et al.

Abstract: IntroductionVery preterm birth is associated with lung function impairment later in life, but several aspects have not been studied. We aimed to comprehensively assess lung function at school age in very preterm infants and term controls, with special emphasis on bronchopulmonary dysplasia (BPD), sex, and bronchodilator response.MethodsAt 12 years of age, 136 children born very preterm (85 with and 51 without BPD) and 56 children born at term performed spirometry, body plethysmography, impulse oscillometry, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… 25–27 Data are presented as per cent of predicted (median and IQR) and as proportion of children outside of normal limits: upper (ULN) and lower (LLN) limit of normal. For impulse oscillometry, airway resistance by body plethysmography, and MBW, normal values were defined from our previous study 28 (see online supplemental file 1 ). In the tables, measurements are reported as absolute values, per cent of predicted normal values (FEV 1 ), z-scores or number of individuals <LLN, >ULN, <5th centile and >95th centile.…”
Section: Participants and Methodsmentioning
confidence: 99%
“… 25–27 Data are presented as per cent of predicted (median and IQR) and as proportion of children outside of normal limits: upper (ULN) and lower (LLN) limit of normal. For impulse oscillometry, airway resistance by body plethysmography, and MBW, normal values were defined from our previous study 28 (see online supplemental file 1 ). In the tables, measurements are reported as absolute values, per cent of predicted normal values (FEV 1 ), z-scores or number of individuals <LLN, >ULN, <5th centile and >95th centile.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…In addition to the spirometric parameters, lung clearance index (LCI), a marker of ventilation inhomogeneity derived from multiple breath washout (MBW), start to be applied in preterm subjects [ 7 ]. In certain studies, LCI was found to be higher in children born very preterm [ 8 ]. Nevertheless, further research is required, particularly among young survivors.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing concern that PLD may predispose an individual to the premature development of chronic obstructive pulmonary disease (COPD) in early adulthood ( 7 , 8 ), with implications for quality of life and life expectancy if lung function deficits continue to track into adulthood. Whilst much research focus has concentrated on the mechanism of respiratory morbidity in those with a history of BPD ( 9 , 10 ), it is increasingly apparent that there is a population of preterm-born subjects who develop PLD despite not having had a diagnosis of BPD in the neonatal period ( 3 , 11 ), with impaired spirometry, altered respiratory mechanics and reduced gas diffusion capacity ( 12 ). Furthermore, other early life risk factors such as gestational immaturity and intrauterine growth restriction are also strongly associated with later adverse respiratory outcomes ( 13 ).…”
mentioning
confidence: 99%
“…Whilst it is well documented that preterm-born subjects generally respond well to short-acting β 2 -agonists, including those with and without a neonatal diagnosis of BPD ( 12 , 23 ), the Pelkonen study assessed two-week course of daily terbutaline administration. Although they did not report post-treatment lung function, they suggested improved diurnal variation of PEFR ( 20 ).…”
mentioning
confidence: 99%